ACADEMIC STRESS TENDENCIES IN ADOLESCENTS - Shalza Arthya Fadia; Nadia Aulia Nadhirah; Ipah Saripah (Jurnal Neo Konseling, 2023)
Stress is part of the human experience. However, adolescents who are facing a period of development will face various pressures and problems that occur in their lives, especially problems and demands for their academics. Adolescents who find it difficult to face these demands will experience problems in psychological and physical problems, of course, this will affect lifestyles and behaviors that endanger their physical and psychological health. The purpose of this study is to describe and analyze various literatures regarding the phenomenon of academic stress in adolescents. The method used in this study is a literature review, by obtaining 500 data taken from google scholar and crossref databases through the Publish or Perish application and then filtered according to the topics to be discussed. The results of this study indicate that adolescents are vulnerable to academic stress due to the difficulty of coping with the academic and learning demands.